Improvement of music education employing innovative methods - Rauduvaitė, Asta (Pedagogika, 2014)
The article discusses possibilities for improvement of music education employing innovative methods of personal meaning and emotional imitation: the topicality of this process while developing value-based attitudes of junior school age children and integrating popular music in the context of theories of pedagogical thought development is substantiated, following the results of the research, the links of school students’ music activities and formation of value-based principles are discussed as well as possibilities for music education improvement in a contemporary school. On the basis of scientific literature analysis, education at present is perceived as an integral process of constant change and continuity, which is purposefully directed towards improvement of relations of an individual with the surrounding world. History of human culture and accumulated pedagogical experience serve as foundation for general music education today, for linking of past and present values of music culture as well as for their nurturance. A considerable number of researchers in general pedagogy tend to ascribe a very important educative function to music but the role of popular music, as a modern cultural phenomenon, remains unrevealed. The conducted research allows to conclude that striving for improvement of content of traditional music education, the methods of personal meaning and emotional imitation are acceptable to develop value-based principles of junior school children through integration of popular music. The idea of personal meaning method enables learners to communicate with music in a way, which creates preconditions for better cognition of oneself and others. Method of emotional imitation enables a learner to pursue a higher goal, i.e., an ability to live using personally created feelings and thoughts. All this is as if a music-based pretext to communicate with oneself and with others creating a possibility for turning back and looking forward. Thus, not only individuality of cognition but also a value-based attitude of a perceiver are revealed.